Assessing Expressive Oral Reading Fluency - Timothy G. Morrison; Brad Wilcox (MDPI AG, 2020)
Educators struggle to assess various aspects of reading in valid and reliable ways. Whether it is comprehension, phonological awareness, vocabulary, or phonics, determining appropriate assessments is challenging across grade levels and student abilities. Also challenging is measuring aspects of fluency: rate, accuracy, and prosody. This article presents a history of fluency in American education with particular focus on assessing expressive oral reading. In addition, the two major approaches to prosody assessment will be explained, and the three most prominent tools for rating expressive oral reading will be analyzed and discussed.